COMBINATION OF MULTILAYER Ag-Al FOR OPTICAL BIOSENSOR BASED ON SURFACE PLASMON RESONANCE - Tan Tai Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
This work presents the simulation and experimental results of a surface plasmon resonance (SPR) sensor made of a hard polymer-clad fiber. The cladding of the fiber is removed, and then a bimetallic film of nanometer thickness is deposited around the fiber core to create a ten-centimeter-long sensing surface. An optical sensor based on thin film combinations of silver and aluminum has a detection capability of about 3×10-6 (dB/RIU), allowing high sensitivity of easily fabricated optical sensors. This leads us to believe that the proposed SPR sensor can be used to detect biological targets during the clinical diagnosis of diseases, e.g., heart disease, Alzheimer’s disease, cardiovascular disease, and stroke.